How Yiddish Polonisms may uncover Iranian, Turkic and other Asian speech in the White Croat State in Galicia - Wexler, Paul (Slavia Centralis, 2022)
As traders on the Silk Roads from the 9–13th centuries, Yiddish speakers acquired about 5,000 Afro-Asian, mainly Persian, linguistic components. In Poland, these Jews, largely of Iranian origin themselves, first settled in or near the Galician White Croat State, which disappeared by the 10th century. As unwritten Iranian and Turkic became obsolete, many such influences, also found in Polish Yiddish, came to be replaced by Polonisms, that resembled the original Iranian and Turkic terms in form and meaning. The present paper will explore how many Polonisms in Polish and Ukrainian Yiddish (essentially "covert Irano-Turkisms") can reconstruct aspects of the extinct Iranian and Turkic once spoken in Slavic and German territories. So far, there is no other means available to us to accomplish this task.